Untersuchungen zum Einfluß von Getreideblattläusen auf die Ertragsbildung bei Winterweizen. - Freier, Bernd; Wetzel, Theo (Contributions to Entomology = Beiträge zur Entomologie, 1976)
Tests on very small plots to determine the damage caused by Macrosiphum avenae (Fabricius) attacing the ears of winter wheat showed that the yield was not significantly influenced by a maximum abundance of less than 30 aphids per inflorescence or by aphid indices (which are based on the density of population throughout the attack) of less than 400. Whith a maximum abundance of more than 40 aphids per ear in the milk stage or with aphid indices higher than 600 there was a hihgt statistical probability of losses gerater than 20 per cent. ...